Influence of perceptions on help-seeking behaviours of male survivors of intimate partner violence. - Oluwayimika Popoola, Babatunde (Universidad Autónoma de Ciudad Juárez, 2022)
The general objective of this project is to explore the lived experiences of men who are survivors of IPV and to also explore the impact and relationship between perception of IPV bias and help/support seeking. This study was conducted using a mixed methods design, it is a cross-sectional research project (both the quantitative and qualitative studies). This study used a mixed approach in which, despite the use of both qualitative and quantitative data collection and analysis methods, they were under the umbrella of a single paradigm, in this case the post-positivist paradigm. The findings from the quantitative study revealed that the perception of male survivors of their experiences of victimisation have an influence on their help-seeking behaviour. The perception of male participants in this study regarding available resources influences their IPV help seeking behaviour. Also, help-seeking behavior of male survivors of IPV in this study is determined by the perception of bias in the programs available for survivors. The qualitative study revealed that help-seeking by male survivors of IPV have been influenced by their perceptions of what the society thinks of them and how they are being cared for by the service providers (i.e., the treatment received from the criminal justice system, the law enforcement, the service providers, influences the help seeking behaviour of men who are survivors of IPV). In conclusion, men who are survivors of IPV also suffer from physical injuries contrary to the general belief that only women suffer from physical injuries. The psychological trauma that follows the horrific events of the abuse live with men for a very long time and destroys their self-esteem, trust as well as damages the relationship they have with their children.